Critical Role for Very-Long Chain Sphingolipids in Invariant Natural Killer T Cell Development and Homeostasis - Saroha, Ashish; Pewzner-Jung, Yael; Ferreira, Natalia S.; Sharma, Piyush; Jouan, Youenn; Kelly, Samuel L.; Feldmesser, Ester; Merrill, Alfred H.; Trottein, François; Paget, Christophe; Lang, Karl S.; Futerman, Anthony H. (Frontiers in Immunology, 2017)
The role of sphingolipids (SLs) in the immune system has come under increasing scrutiny recently due to the emerging contributions that these important membrane components play in regulating a variety of immunological processes. The acyl chain length of SLs appears particularly critical in determining SL function. Here, we show a role for very-long acyl chain SLs (VLC-SLs) in invariant natural killer T (iNKT) cell maturation in the thymus and homeostasis in the liver. Ceramide synthase 2-null mice, which lack VLC-SLs, were susceptible to a hepatotropic strain of lymphocytic choriomeningitis virus, which is due to a reduction in the number of iNKT cells. Bone marrow chimera experiments indicated that hematopoietic-derived VLC-SLs are essential for maturation of iNKT cells in the thymus, whereas parenchymal-derived VLC-SLs are crucial for iNKT cell survival and maintenance in the liver. Our findings suggest a critical role for VLC-SL in iNKT cell physiology.